Positive predictive value of CD200 positivity in the differential diagnosis of chronic lymphocytic leukemia. Issue 5 (6th November 2019) - Sorigue, Marc; Magnano, Laura; Miljkovic, Milos D.; Nieto‐Moragas, Javier; Santos‐Gomez, Mireia; Villamor, Neus; Junca, Jordi; Morales‐Indiano, Cristian
Abstract: Background: The role of CD200 in the differential diagnosis of chronic lymphocytic leukemia (CLL) and classical mantle cell lymphoma (MCL) is well established. Its role in the differential diagnosis of CLL and other lymphoproliferative disorders (LPD) is less clear, in particular its positive predictive value (PPV). Materials and methods: We conducted a systematic review of the use of CD200 in the differential diagnosis of CLL, MCL, and other predominantly leukemic, typically CD103‐negative LPD. With the results, we then derived a curve to determine the PPV based on the prevalence of the disorders included in the differential diagnosis. Results: Of 43 publications screened, 27 were included in the systematic review (5, 764 patients). The median CD200 positivity rate in all studies and the percentage of CD200‐positive (pooled) patients was 100% and 95% (3, 061/3, 208) in CLL, 4 and 8% (86/1112) in MCL and 56 and 62% (425/689) in other LPD. Conclusion: CD200 is suboptimal for the differential diagnosis of CLL and disorders other than nodal MCL.